DEVELOPMENT OF PROJECT BASED OUTDOOR LEARNING TOOLS IN GEOMETRY TO IMPROVE STUDENTS' PROBLEM SOLVING ABILITY - Masrukan Masrukan; Ernita Ernita (Aksioma: Jurnal Program Studi Pendidikan Matematika, 2024)
The teaching tools are crucial for teachers in delivering instructional material. However, the development of learning tools that meet content standards and are of high quality is still quite rare. This research aims to develop and evaluate the quality of Project-Based Outdoor Learning (PjBOL) tools for geometry to enhance problem-solving skills. The research sample consists of students from classes VII D and VII E at SMP Negeri 2 Ungaran. The research method used is Research and Development with the Four-D model: Define, Design, Develop, Disseminate. The research instruments include expert assessment sheets, student response sheets, and problem-solving ability tests. Data analysis focuses on validity, practicality, and effectiveness. The results indicate that: (1) the developed PjBOL tools include Learning Objectives Flow, Teaching Modules, and Learning Materials for geometry to enhance problem-solving skills; and (2) the PjBOL tools are of high quality as they meet the criteria of validity, practicality, and effectiveness. The test results show that the problem-solving abilities of students using PjBOL are higher in average and proportion compared to those using Discovery Learning, and there is an improvement in students' problem-solving abilities. Based on these findings, PjBOL tools effectively enhance problem-solving skills.